STRATEGI PROMOSI PAKET WISATA PT. KIRANA SURYA GEMILANG (KIRANA TOUR) YOGYAKARTA - , FENDY WIDIATMAKA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
At this time, development in tourism sector give benefits for people because tourism sector is one of the development sector in economics. Tourism activities are one of the non-oil and gas sector which give major contribution for Indonesia economy. Economy crisis that happened in Indonesia doesnât affect negative impact for Indonesia Tourism industry. Indonesia Tourism industry exactly increased from year to year. Thatâs proven with enchantment growth in the number of tourists and travel agencies who make and sell the package tour. Based on that reason, so The Writer want to know how the promotion strategy to increase customer in travel agencies. The other purpose of this writing is what the problem of making are promotion activities and how the strategy promotion can increase sales of package tour. Promotion strategy is one of the urgent marketing parts to increase sales of package tour in the travel agencies. As a part of package tour marketing, promotion give the positive impact to increase sales of product and services through promotion method like online promotion, advertisement, direct promotion, and public relation. Therefore package tour promotion strategy is very important in the travel agencies.